2006
DOI: 10.1158/1078-0432.ccr-06-0145
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of an Allogeneic Cellular Immunotherapy in Hormone-Naïve Prostate Cancer

Abstract: Purpose: To determine the toxicity, immunologic, and clinical activity of immunotherapy with irradiated, allogeneic, prostate cancer cells expressing granulocyte macrophage colony-stimulating factor (GM-CSF) in patients with recurrent prostate cancer. Patients and Methods: A single-institution phase I/II trial was done in hormone therapy^naI« ve patients with prostate-specific antigen (PSA) relapse following radical prostatectomy and absence of radiologic metastases.Treatments were administered weekly via intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 37 publications
0
76
0
1
Order By: Relevance
“…These cell lines were modified with a human GM-CSF gene to secrete high levels of bioactive GM-CSF. An initial phase 1/2 trial in hormone-naBve patients with prostate cancer showed a favorable safety profile, statistically significant changes in the slope of prostate-specific antigen (PSA) velocity, and a PSA decline of >50% in one patient, suggesting an antitumor effect (13).An open-label, phase 1/2, multicenter trial was therefore conducted to evaluate the safety, clinical activity, and immunogenicity of the GM-CSF -secreting, allogeneic cellular immunotherapy in chemotherapy-naBve patients with metastatic HRPC. The protocol was amended to allow administration of a higher dose level after an interim analysis showed that the initial dosage tested was well tolerated.…”
mentioning
confidence: 99%
“…These cell lines were modified with a human GM-CSF gene to secrete high levels of bioactive GM-CSF. An initial phase 1/2 trial in hormone-naBve patients with prostate cancer showed a favorable safety profile, statistically significant changes in the slope of prostate-specific antigen (PSA) velocity, and a PSA decline of >50% in one patient, suggesting an antitumor effect (13).An open-label, phase 1/2, multicenter trial was therefore conducted to evaluate the safety, clinical activity, and immunogenicity of the GM-CSF -secreting, allogeneic cellular immunotherapy in chemotherapy-naBve patients with metastatic HRPC. The protocol was amended to allow administration of a higher dose level after an interim analysis showed that the initial dosage tested was well tolerated.…”
mentioning
confidence: 99%
“…In the GVAX product, further cell division is prevented through irradiation. [34][35][36][37] This whole-cell approach enables multiple tumor antigens to be targeted simultaneously and large quantities of vaccine to be manufactured.…”
Section: Sipuleucel-t: the First Antigen-presenting Cell (Apc)-based mentioning
confidence: 99%
“…The injection sites were found to have invasion of inflammatory cells and APCs on histopathology. At 20 weeks after the first treatment, 16 of 21 treated patients showed a statistically significant decrease in PSA velocity (slope) compared with prevaccination PSA course (Simons et al, 2006) (Urba et al, 2008). Two further uncontrolled single-arm phase II studies included asymptomatic CRPC patients with (n = 34) or without (n = 21) metastases (G9803 trial) and only men with metastases (n = 80) (G0010 trial).…”
Section: Prostate Gvax®mentioning
confidence: 99%
“…sipuleucel-T) xenogeneic PAP as target (Higano et al, 2009a;Kantoff et al, 2010a) (Fong et al, 2001) 1.1.3 Allogeneic whole-tumor cells (modified ex vivo) PSMA as target (Tjoa et al, 1999;Fishman, 2009) e.g. GVAX (Simons et al, 2006;Higano et al, 2008;Higano et al, 2009b) PSA as target (Barrou et al, 2004) (Hildenbrand et al, 2007) e.g. OnyP (Michael et al, 2005) PSCA as target (Thomas-Kaskel et al, 2006) e.g.…”
Section: Introductionmentioning
confidence: 99%